What Is Development? What Is Progress? The Social Science and Humanities of Utopia and Futurology. Issue 2 (June 2014) - Lempert, David
The process of "modernization" or "development" in contemporary globalization has included an assault on imagination, such that the very idea of offering alternative visions seems to be taboo. This article advocates for a constructive return to alternative models of human and social development based on realistic assumptions, human hopes, and measures of progress in both social sciences and humanities, to rejuvenate what has become a dying, impoverished, and stultifying, if not useless area of study. The article uses two relatively recent books with alternative examinations of utopia – one on early Russian science fiction and one from the literature of architecture and gender – as springboards for a discussion of what is wrong and what can be changed in the field of development studies.